Identification of the Genotypes Circulating in the Ecuadorian Population Infected with the Hepatitis C Virus (HCV) - Moncayo M; Teran E; Reyes J; Yerovi G; Robalino M; Aguilar AC; Garzon-Chavez D (Dove Medical Press, 2023)
Miguel Moncayo,1,2 Enrique Teran,1,3 Jorge Reyes,4,5 Gabriela Yerovi,6 Marcia Robalino,6 Ana Cristina Aguilar,1,3 Daniel Garzon-Chavez1,3 1Instituto de Microbiología, Universidad San Francisco de Quito USFQ, Quito, Ecuador; 2Laboratorio Clinico Pasteur Dr. Alberto Moncayo Calero, Quito, Ecuador; 3Colegio de Ciencias de la Salud, Universidad San Francisco de Quito USFQ, Quito, Ecuador; 4Facultad de Ciencias Químicas, Universidad Central del Ecuador, Quito, Ecuador; 5Departamento de Microbiologı´a, Hospital del IESS Quito Sur, Quito, Ecuador; 6Ministerio de Salud Pública del Ecuador, Quito, EcuadorCorrespondence: Daniel Garzon-Chavez, Email dgarzonc@usfq.edu.ecIntroduction: The hepatitis C virus (HCV) is responsible for 1.5 million new infections, and around 290 thousand deaths worldwide. 15 to 30% of the patients that go into a chronic phase of the disease will develop cirrhosis or hepatocellular carcinoma within 20 years and is the leading etiology for liver transplantation. HCV genetic characteristics display a remarkable genetic diversity, which divides HCV into 8 genotypes and 67 subgenotypes; the treatment and probability of chronic HCV depend on these genotypes and subgenotypes. In Ecuador, there is no available information regarding HCV genotypes and subgenotypes; therefore, this study aims to provide an overview of the main genotypes circulating in Ecuador.Methods: In a cross-sectional and descriptive study using the Ecuadorian Ministry of Health (MSP) registry of patients already diagnosed with Hepatitis C (HCV) between 2017 and 2019. From 51 patients identified by health ministry, blood samples from a total of 15 subjects (named HCV1 to HCV15) were collected using an appropriate venipuncture technique. Pandemic-related circumstances avoid reaching all patients identified by health ministry.Results: After the amplification of 11 samples from patients living in the Ecuadorian territory, the genotypes of HCV obtained were distributed as follows: 6 samples corresponding to subgenotype 2b (54.5%), 2 samples corresponding to subgenotype 1a (18.2%), 2 samples corresponding to subgenotype 4d (18.2%) and 1 corresponding to sample 1b (9.1%).Conclusion: These results represent the first epidemiological approach to genotype distribution in Ecuador, and it contributes to better management of patients. We emphasize the importance of the development of better strategies from the Healthcare Ministry of Ecuador (MSP) for the identification, treatment and tracking of HCV patients.Keywords: hepatitis C virus, hepatitis C genotype, hepatitis C subgenotype, hepatitis C prevalence, cirrhosis, hepatocellular carcinoma